The Experience of Locomotor Training From the Perspectives of Therapists and Parents of Children With Cerebral Palsy - Dayna Pool; Dayna Pool; Dayna Pool; Catherine Elliott; Catherine Elliott; Catherine Elliott; Claire Willis; Ashleigh Thornton; Ashleigh Thornton (Frontiers Media S.A., 2021)
Objective: The objective of this study was to explore the experiences of intensive locomotor training from the perspective of therapists and parents of children with cerebral palsy.Design: A qualitative study using semi-structured interviews was employed to capture perspectives following an intensive locomotor training intervention. Data were analyzed thematically, systematically coding and interpreted by grouping information into themes and sub-theme categories.Participants: Five therapists and seven parents of children with high daily physical assistance and equipment needs participated in the study.Setting: A pediatric tertiary hospital.Results: Experiences of locomotor training were described with relation to the suitability of locomotor training with sub-themes of intervention length and time, engagement within sessions, the importance of support, and the utility of locomotor training beyond a research context. Motivation for participating in locomotor training was described in relation to the enjoyment of movement and for increasing activity level. The barriers and facilitators who participated in locomotor training provided environmental and personal factor subthemes. Finally, the outcomes from the intervention were related to improvements in physical health, sleep, affect and emotion, and ambulation in daily activities.Conclusion: The experience of intensive locomotor training from the perspectives of parents of children who have high physical assistance and equipment needs and the therapists providing the intervention was described. Future studies should consider outcome measures beyond motor capacity to quantify the perceived outcomes of interventions that are meaningful to families.